1996
DOI: 10.1017/s1074070800007288
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Risk Management Properties of Grazing Contracts Versus Futures and Option Contracts

Abstract: A stochastic budget simulator and generalized stochastic dominance are used to compare the risk management properties of grazing contracts to futures and option contracts. The results show that the risks of backgrounding feeder cattle are reduced significantly for pasture owners in a grazing contract. However, the risks of the cattle owner in a grazing contract are not significantly reduced. The results also show that generally risk averse pasture owners prefer grazing contracts to integrated production when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Research on economic returns under contract grazing has been limited. Harrison et al (1996) found that contract grazing can reduce risk for the cattle caretaker. Anderson et al (2004) found that direct ownership results in higher returns per hectare than contracting, but also the most variable returns.…”
mentioning
confidence: 99%
“…Research on economic returns under contract grazing has been limited. Harrison et al (1996) found that contract grazing can reduce risk for the cattle caretaker. Anderson et al (2004) found that direct ownership results in higher returns per hectare than contracting, but also the most variable returns.…”
mentioning
confidence: 99%
“…However, all three systems had high probabilities of receiving negative returns, ranging from 25% for the NT system to 55% for the CT system, and minimum returns ranged from -$435 ha -1 (-$176 ac -1 ) for CT to -$354 ha -1 (-$143 ac -1 ) for RT. Much of the risk associated with stocker grazing on winter wheat pasture may be attributed to the large level of capital required to purchase calves (Anderson et al 2004) and the highly volatile nature of cattle prices (Harrison et al 1996). The large riskiness associated with stocker grazing on winter wheat forage may be one reason why the practice is not more extensively used in Arkansas.…”
Section: Conventional Tillage Reduced Tillage No-tillagementioning
confidence: 99%
“…The caretaker receives a fee (either a fee per unit of gain or a flat charge fee for each day the animal is on the caretaker's pasture or both) from the cattle owner. Contract grazing provides limited farmers with a means of utilizing winter forage without having to buy the animals (Anderson et al 2004) and removes all risks associated with the market (Harrison et al 1996). However, tradeoffs may exist between the reduced return variability associated with contract grazing and the higher expected returns associated with full ownership.…”
Section: Conventional Tillage Reduced Tillage No-tillagementioning
confidence: 99%
“…One result, as noted above, is that the net prices for corn and soybeans, from the various advisers, have a wide range and that the advisers' performances are rarely consistent from year to year (Irwin et al, 2000). Harrison, Bobst, Benson, and Meyer (1996) compared the profitability and risk-management properties of grazing contracts to futures and option contracts for backgrounding (or stocking) operations (assemble and grow calves from weaning weights to feed-lot-ready weights) in the feeder-cattle industry. Net return distributions from 28 different backgrounding production and marketing arrangements were evaluated under simulated cash, futures and options prices and animal performance, and ranked using stochastic dominance.…”
Section: Performance Of Marketing Strategiesmentioning
confidence: 99%